2022
DOI: 10.3390/su15010368
|View full text |Cite
|
Sign up to set email alerts
|

Blue Carbon: Comparison of Chronosequences from Avicennia marina Plantation and Proteresia coarctata Dominated Mudflat, at the World’s Largest Mangrove Wetland

Abstract: Sundarban is the world’s largest contiguous mangrove forest but is under threat from anthropogenic interventions. Plantations are the favored method to restore degraded mudflats. In this study, ecological functional soil indicators (available N, soil organic C, available P, salinity) and service (Blue carbon pool) of the iteroparous tree Avicennia marina (Forssk.) Vierh. (Acanthaceae family), plantation has been compared with a natural mudflat dominated by mangrove semelparous grass Proteresia coarctata (Roxb.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 50 publications
3
3
0
Order By: Relevance
“…Previous research has highlighted the presence of zonation at the Indian Sundarbans from low tide level (LTL) to high tide level (HTL) [46,47]. In the present study, a similar zonation was observed in the study site.…”
Section: Variations In Mangrove Diversitysupporting
confidence: 85%
“…Previous research has highlighted the presence of zonation at the Indian Sundarbans from low tide level (LTL) to high tide level (HTL) [46,47]. In the present study, a similar zonation was observed in the study site.…”
Section: Variations In Mangrove Diversitysupporting
confidence: 85%
“…The sediment OM range observed from surface to 30 cm depth in pre-monsoon (3.12-11.47%) and post-monsoon (3.44-12.68%) seasons in this study are within and higher than the sediment OM range observed for other saltmarsh species (4.13-7.13%) from the east coast of India (Kaviarasan et al, 2019), but lower than sediment OM (4.9-16.9 %) observed from Gulf of Kutch, Gujarat on India's west coast (Jagtap et al, 2002). Similarly, the variation observed in this study for high sediment Corg in post-monsoon (2.42-13.44%) compared to pre-monsoon season (2.03-12.31%) has also been observed in the P. coarctata meadows from the Bhitarkanika National Park (0.64-2.71%), from Sundarbans (2.0-4.0%) (Banerjee et al, 2022;Chowdhury et al, 2023), and other mixed saltmarsh species (2.18-3.81%) ecosystems of India (Kaviarasan et al, 2019). The higher sediment Corg in our study sites could be due to higher autochthonous contribution from P. coarctata associated plant materials (roots, rhizomes and leaves) and sediment trapping capacity of these plants due to their high densities at locations like Dhamra and Astaranga.…”
Section: Influence Of Physical Parameters On the Sediment Variables (...supporting
confidence: 83%
“…This study, followed a similar pattern for blue carbon ecosystems, with sediment Corg contributing >70% of the ecosystem Corg stocks, and P. coarctata total biomass (AG +BG) contributing 30% in pre-monsoon and 29% in postmonsoon season (Figure 7). This variation in sediment and biomass contribution towards total ecosystem carbon stocks has also been observed for P. coarctata meadows along the east coast that are adjacent to mangrove ecosystems (Banerjee et al, 2022;Begam et al, 2017;Chowdhury et al, 2023) and with other mixed saltmarsh species from the coast of India (Kaviarasan et al, 2019). In this study, the highest mean sediment Corg stocks were observed in the mono-specific patches of P. coarctata meadows of Astaranga (57.04 ±5.99 Mg C), which is 1.3-fold higher than previously observed sediment Corg stocks for P. coarctata meadows of the Mahanadi delta (44.79 ± 0.23) and the Bhitarkanika National Park (42.08 ± 1.15) that are adjacent or mixed with various mangrove species (Table 2).…”
Section: Influence Of Physical Parameters On the Sediment Variables (...supporting
confidence: 68%
“…The fundamental drivers for reducing the total blue carbon stock of the Sundarban, the world's largest contiguous mangrove forest, are recurrent tropical cyclones, soil erosion, anthropogenic pollution, and so on [253]. Plantations of iteroparous mangrove species may provide an effective solution to these challenges [254]. Furthermore, it is proposed that living shorelines that incorporate blue carbon ecosystems into their design could sustain and/or increase carbon stocks and carbon sequestration capacity in Australia [150].…”
Section: Currently Researched Topicsmentioning
confidence: 99%